Application of developmental games based on kinesthetic perception to improve proprioceptive sensitivity, intelligence and cooperation in primary school children - Aulia Maris Syahputri; Pamuji Sukoco Sukoco (H.S. Skovoroda Kharkiv National Pedagogical University, 2020)
Aim: to produce a game learning model based on kinesthetic perception to improve kinesthetic perception, play intelligence, and collaboration among elementary school children. Material and methods. The game learning model based on kinesthetic perception is adapted to the growth and development aspects of students which is packaged through the processing of limbs that is focused on the psychomotor domain consisting of a series of basic locomotor movements, manipulative, non-manipulative, cognitive play intelligence, and effective cooperation. The method used is research and development, namely descriptive, evaluative and experimental methods. This research method is used to produce a product, namely a game learning model based on the kinesthetic perception of children aged 7-8 years which is equivalent to lower grade elementary school students. Development procedures: (1) collecting research results and information, (2) analyzing the product to be developed, (3) developing the initial product, (4) conducting expert validation, (5) conducting small-scale trials and revisions, (6) conducting large-scale trials and revisions, (7) making final products, and (8) conducting effectiveness tests. The subjects of this study were grade 1 elementary school students. The data analysis techniques used were quantitative and qualitative descriptive analysis. The final product effectiveness test used one group pretest-posttest design experiment. Results. The results of this study are in the form of a kinesthetic perception-based game learning model to improve kinesthetic perception, playing intelligence, primary school children's collaboration which contains four games, namely (1) Target Shooting Games, (2) Train Car Games, (3) Flag Games, and ( 4) Rakartugu Games. From the results of the assessment of experts and practitioners, the game learning model based on kinesthetic perception has a validity of 0.963. Conclusions. Kinesthetic perception based game learning model is effective for developing kinesthetic perception limb processing skills, playing intelligence and cooperation.